A/r/tography and Visual Arts Based Educational Research - Marín-Viadel, Ricardo; Roldán, Joaquín (Arte, Individuo y Sociedad, 2019)
The goal is to epistemologically ground a/r/tography in the context of arts-based research methodologies. Arts-Based Research appeared in 1993, driven by Elliot Eisner, as an intensification of the aesthetic qualities of educational research processes and outcomes. It has developed bringing human and social sciences research closer to artistic creation (despite epistemological positions, such as those of H. Gardner, which bluntly separate the arts from science). Its fundamental characteristic is the use of ideas and forms of representation provided by the arts to do research. One of the methodological modalities of Arts-Based Research is A/r/tography, which appeared in 2003 driven by Rita Irwin, as a coherent and balanced unification of artistic, educational and research purposes. Its fundamental methodological concepts are vital inquiry, metaphors and metonymies, reverberations and the search for meaning in the combination of texts and images. Both Arts-Based Research and A/r/tography used any artistic specialty (dance, literature, music, theatre, visual arts, etc.), therefore become the meeting zone between qualitative methodological innovations in human and social sciences, and the community based and participatory trends of contemporary art, such as ‘Artivism’.
Keywords: Arts based research; A/r/tography; art education; visual arts